PENERAPAN MODEL PEMBELAJARAN COOPERATIVE LEARNING TEKNIK TWO STAY TWO STRAY DENGAN MEDIA KARTU SOAL UNTUK MENINGKATKAN KEAKTIFAN DAN KESADARAN SEJARAH - Iswanti, Rani Puspo; S, Leo Agung; Wahyuni, Sri (Candi, 2017)
This research is aimed to improve the students? activeness and historical awareness of the class XI IPS 1 of SMA Negeri 3 by implementing Two Stay Two Stray (TSTS) cooperative learning Method using question card.This is a Classroom Action Research (CAR). This research was carried out by two cycles. Each cycle consists of planning, action, observation, and reflection. The subject of this research is the 22 students of the class XI IPS 1 of SMA Negeri 3 Surakarta. The data were collected from the teacher, students, and learning process. The data were collected by test, observation, interview, documentation, and questionnaire. The data were analyzed by using interactive model which consists of some steps: reducing data, presenting data, and making conclusion or verification.The result of this research showed that the learning process was done well. In the pre-research, the percentage of the activity accomplishment was 78.14%, increased to 87.51% in the 1st cycle, and increased to 94.77% in the 2nd cycle. The students? activeness in the pre-research was 71.51%, increased to 77.87% in the 1st cycle, and increased to 85.30% in the 2nd cycle. The students? historical awareness was 77.63% in the pre-research, increased to 78.84% in the 1st cycle, and increased to 81.30% in the 2nd cycle.Based on the result of the research, it can be concluded that teaching history using Two Stay Two Stray (TSTS) cooperative learning Method which uses question card is able to improve the students? activeness and historical awareness of the class XI IPS 1 of SMA Negeri 3 Surakarta.